Promoting Child-Friendly Schools through the Merdeka Curriculum: A Critical Evaluation of Magelang Regency, Indonesia - Rasidi, Rasidi; Subur, Subur (International Journal of Contemporary Studies in Education, 2024)
To promote Child-Friendly Schools through the Independent Curriculum in Magelang Regency, this research reveals several challenges and opportunities. The study used a sequential mixed methods approach to surveying 47 teachers and 100 students, in-depth interviews with 20 school principals and 20 key informants, and participant observation in 10 schools. The findings show that implementing a child-friendly school is still early, facing various obstacles such as limited understanding of teachers and school staff about the concept of a child-friendly school, limited resources, and a school culture that still needs to be fully supportive. Nonetheless, the Merdeka Curriculum offers significant opportunities to strengthen child-friendly schools by emphasizing child-centred learning, collaboration, and character development. Integrating child-friendly school principles into the Independent Curriculum and developing the capacity of teachers and school staff are crucial steps needed to create genuinely child-friendly schools. This research provides important insights for education stakeholders to improve and holistically increase the holistic implementation of child-friendly schools in Magelang Regency.